Cambodia : Quality Basic Education for All - World Bank (Washington, DC, 2012)
The Government of Cambodia's education sector program has affected positive change including a marked increase in primary net enrollment rates. Despite improvements, however, the Government faces formidable challenges in consolidating and furthering these gains towards achieving quality basic education for all. To address these challenges, the Ministry of Education, Youth, and Sport has recently revised its Education Strategic Plan 2004/2008. This report aims to contribute and inform the ongoing debate on policy options by providing a comprehensive empirical analysis of the role of demand- and supply-side factors and policy interventions in facilitating access to, completion of, and learning in basic education, especially for the most disadvantaged children. The report is divided into three main parts. The first part presents a profile of the basic education sector. The second part provides a general characterization of how demand and supply factors are related to student outcomes, and draws policy implications from the results. The third part exploits the valuable lessons from past and ongoing demand- and supply-side interventions in Cambodia. The report and its findings highlight the importance of exploiting all existing sources of education data, and conducting rigorous impact evaluations of key strategic policy interventions for future education policy and planning.